Trends in lipase immobilization: Bibliometric review and patent analysis. (November 2021) - Almeida, Francisco Lucas Chaves; Castro, Maria Paula Jiménez; Travália, Beatriz Medeiros; Forte, Marcus Bruno Soares
Graphical abstract: Highlights: Bibliometric and patent analysis of lipase immobilization techniques. China, India, and Brazil stand out as the most academically productive lipase immobilization research. Immobilization process may increase lipase activity. Immobilized lipases are widely used in the hydrolysis and transesterification reactions to produce biodiesel and flavor-esters. Abstract: Enzymes have great industrial potential as biocatalysts, particularly lipases, which have attracted much attention for their extensive applications. As the use of enzymes becomes more widespread, a variety of enzyme immobilization methods are being developed for enhanced performance. This review provides a bibliometric and patent analysis of lipase immobilization techniques. Scientific papers and patents were searched in Web of Science and World Intellectual Property Organization databases, respectively. The results showed that immobilized lipases are being extensively used for the production of flavor esters and biodiesel. China, India, and Brazil, as well as institutions related to these countries, stand out as the most academically productive in terms of lipase immobilization research. It was also found that many researchers and journals focused exclusively on this field. Patent analysis revealed a large number of filed patents, indicative of the industrial potential of immobilized lipases. These findings underscore the importance of research on lipase immobilization for a diversity of applications.